Identifikasi Sikap Toleransi Antar Umat Beragama di Lingkungan Sekolah Dasar - Nursakinah; Lidia Histuti; Ninda Silvia; Parasian Sinambela (Journal of Basic Education Research, 2022)
Purpose of this Research: This study aims to determine the tolerance attitude of students in class V C. Research Methods: This research is qualitative research, and the type of research is a case study. Researchers focus on an event or phenomenon. This research was conducted in SD Negeri 027/XI Kampung Diilir. The sampling technique was random sampling. Main Findings: The results of this study show that students have implemented an attitude of tolerance. Students and teachers are always cohesive in maintaining harmony in the classroom and school environment. Novelty in this Research: The novelty of this research is to identify the attitude of tolerance possessed by students. The novelty of this research is to find out how the tolerance attitude of students in class V C SD Negeri 027/XI Kampung Diilir.